Joint Determinants of Monetary, Macroeconomic, Social and Income Inequality - Abdulrahman Taresh A.; Dyah Wulan Sari; Rudi Purwono (Muhammadiyah University Press, 2020)
This study discusses all the potential relationships between monetary, macroeconomic, social and income inequality in an integrated manner by making Indonesia a concrete case study. This empirical study discussed the relationship based on theoretical modelling and carried out through appropriate estimators applied to the data of 33 provinces in Indonesia. To achieve this objective, the simultaneous model of seemingly unrelated regressions (SUR) was used. The results concluded that there are variables that jointly determined the monetary, macroeconomic and social also income inequality. Like, consumption can increase inflation and macroeconomic while at the same time can reduce population growth and human development, and increases income inequality. Savings which determine credit also pushes macroeconomics while simultaneously increasing population growth, and it can reduce income inequality. Minimum wages can reduce inflation and encourage production growth, while increases human development and reduces population growth also can reduce income inequality. Unemployment can also reduce inflation and increase economic growth, at the same time reduces population growth and human development while increases income inequality. Education and health encourages economic growth and the level of human development then can reduce income inequality.